Indiana University Maurer School of Law : The First 175 Years - Fariss, Linda K., 1951-; Buckley, Keith A. (Book collections on Project MUSE., 2019)
"In the course of its 175-year history, the Indiana University Maurer School of Law has grown, diversified, and flourished, becoming a law school nationally recognized for its excellence. With innovative and dedicated leadership, the school has emerged into the 21st century stronger than ever. Today it has partnerships with leading institutions in the world and an alumni base that spans the globe. Preparing students for the practice of law, promoting the best interests of society, and taking a leadership role in providing solutions to society's most pressing problems are among the many achievements of the school and its faculty. Filled with historical photographs and engaging sidebars, this book tells the story of the individuals who built, sustained, and strenghtened the Indiana University Maurer School of Law."--Print book jacket